2012
DOI: 10.1515/cclm-2011-0896
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1 and paraoxonase-1 and 3 levels in patients with sepsis treated in an intensive care unit: a preliminary report

Abstract: We observed an inverse pattern between changes in MCP-1, and PON1 and PON3 levels in patients with sepsis, this was related to the resolution of their infection after receiving treatment in an ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
12
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
6
12
4
1
Order By: Relevance
“…In our study PON1 activities were lower in patients with higher APACHE II and SOFA scores. Our data are in contrast with results from Novak et al who did not find statistically significant correlation between PON1 activities and disease severity scores [20], while Sans et al found this correlation to be significant only after recovery from sepsis [21]. …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study PON1 activities were lower in patients with higher APACHE II and SOFA scores. Our data are in contrast with results from Novak et al who did not find statistically significant correlation between PON1 activities and disease severity scores [20], while Sans et al found this correlation to be significant only after recovery from sepsis [21]. …”
Section: Discussioncontrasting
confidence: 99%
“…We have also found that both POase and DZOase activity were lower in surgical patients with sepsis than in healthy controls. In the study of Sans et al, POase activity significantly decreased between admission to ICU and the following day but remained unchanged for the next 4 days [21]. In our study, low PON1 activity did not significantly change during first 5 days of disease.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…However, there is a paucity of information on alterations in plasma CCL2 concentrations in infectious diseases. Recent studies reported that CCL2 levels are elevated in patients admitted to Intensive Care with sepsis, and in patients carrying an indwelling central venous catheter [9,29]. Results from the present investigation conclude that this is also the case in patients carrying an indwelling urinary catheter.…”
Section: Discussionsupporting
confidence: 75%
“…Again, the combined regimen clearly exceeded the effect obtained by single inhibition of CD14 ), indicating the advantage of the combined regimen as compared to single inhibition of CD14. The attenuating effect on MCP-1 also implicates a possible clinical relevance as the level of this chemokine appears to be positively related to severity of sepsis (Sans et al 2012).…”
Section: Discussionmentioning
confidence: 89%